Assessing Participation Among Stroke Survivors: A Systematic Review of Patient-Reported Outcome Measures - Benyamin Hamid; Mahnaz Hejazi Shirmard; Seyedeh Maryam Shafighi Kuzani; Marzieh Pashmdarfard (Occupational Therapy International, 2025)
Conclusion: The identified gaps illustrate the need for more comprehensive measures that accurately capture stroke survivors’ diverse experiences. Improving these assessments is essential for informing clinical practice and rehabilitation strategies, ultimately enhancing patient engagement, satisfaction, and quality of life and improving rehabilitation outcomes for stroke survivors.